Green Supply Chain Management Practice and Performance of Manufacturing Companies in Batu Pahat, Johor - Alina Shamsuddin; Wan Nurul Karimah Wan Ahmad; Leong Chun Peng (International Journal of Supply Chain Management, 2020)
Environmental issues such as air and water pollutions are increasing because of the speedy growth of industrial modernization especially in the manufacturing industry. The industry is considered as one of the main sources of environmental problems. Green supply chain management (GSCM) practices can help companies in the industry improve firm sustainability performance through reduction of environmental risk, at the same time, provide economic and environmental benefit. In Malaysia, researchers were more focused on internal environmental management practices such as the implementation ISO 14001 and the number of research on GSCM practices is still low. This research aims to explore GSCM practices and sustainability performance through a survey among manufacturing companies in Batu Pahat, Johor. It also compares the practices and performance of two case companies using data gathered from interviews. The findings reveal that the manufacturing companies in Batu Pahat had a moderate level of GSCM implementation and sustainability performance. The GSCM practices that companies should focus more are internal environmental management and reverse logistics.